The Effect of Welding Speed on the Weld Seam Profile in MAG and TIG/MAG Hybrid Arc Welding - Uzun, A. (Walter de Gruyter GmbH, 2017)
Abstract The effect of welding speed on the weld seam profile in MAG and TIG/MAG hybrid arc welding was investigated in a low carbon steel. AISI 1020 steel materials having 5 mm thickness were used in the experiments. A fixed MAG and TIG welding currents (90 A and 100 A, respectively) and three different welding speeds (0.14, 0.21 and 0.30 m/min) were selected for welding process for a 100 mm long weld. The welded specimens were cut into several cross-sections; then metallographic tests were performed. The effect of TIG/MAG hybrid arc welding process was compared with the conventional MAG welding. The study showed that welding speed and the selected method have influence on the penetration and that the ratio of penetration depth / weld seam width is increased with increasing welding speed. This increase is more pronounced in TIG/MAG hybrid arc welding compared to conventional MAG welding. The microstructure of the weld metal was also changed relatively by variation of welding speed. With all welding parameters, the weld metal hardness is higher than hardness of the HAZ and the base metal.
Keywords: 13. Climate action; 7. Clean energy